Implementation of the discovery method in teaching newton’s second law for physics education students - Kristiani; Paulo Alves Cabral; Pedro Correia (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
This study examines the implementation of the Discovery Learning method in Micro Teaching courses for Physics Education students at Universidade Nacional Timor Lorosa’e (UNTL). Discovery Learning is a student-centered approach that encourages learners to construct their own understanding through experimental activities, while the teacher serves primarily as a facilitator. The purpose of this research is to determine whether this method can be easily understood and applied by students. This study employs a qualitative design with a case study approach. Data were collected through classroom observations and documentation analysis, then analyzed descriptively to identify patterns in student performance and teaching practices. The findings reveal that most students were able to design systematic lesson plans based on the Discovery Learning framework. However, a small number of students experienced difficulties in implementing the method sequentially during teaching practice. Despite these challenges, the use of simple and easily accessible materials proved that the method can be effectively applied in classroom settings. Overall, the study concludes that Discovery Learning is feasible and beneficial for Micro Teaching students, as it promotes deeper conceptual understanding, particularly in learning complex topics such as Newton’s Second Law